Dynamics of Job Satisfaction Among Contract-Based Employees: The Role of Commitment and Work Environment at the Education Office of South Buru Regency - Wahyudi, Indra; Afsoh, Fradana Firdiantoni; Zakaria, Syawal; Ollong, Kingsly Awang; Latocinsina, Yudhy Muhtar; Henaulu, Agung K.; latuconsina, Bay (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The vital role of contract-based employees (honorer) in supporting the operational and administrative functions of local government education offices is often accompanied by employment uncertainties, potentially affecting their job satisfaction. This study aims to analyze the influence of organizational commitment and the work environment on the job satisfaction of contract employees at the Education Office of South Buru Regency. Employing a quantitative associative approach, data were collected from 100 respondents and analyzed using multiple linear regression. The results indicate that both employee commitment and the work environment have a significant positive effect on job satisfaction. However, the work environment demonstrates a stronger influence (β = 0.739, p = 0.000) compared to organizational commitment (β = 0.094, p = 0.016). The regression model explains 91.6% of the variance in job satisfaction (R² = 0.916). This study concludes that to enhance the job satisfaction of contract employees, management interventions should prioritize creating a supportive and conducive work environment while simultaneously fostering organizational commitment. These improvements are essential for enhancing individual well-being and the overall quality of educational services.